Dermatitis due to self-aggressive behaviors in pediatric age. - Paradisi, M.; Pedicelli, C.; Paradisi, A.; El Hachem, M.; Rota, C.; Burroni, A.G.; Andreoli, E. (European Journal of Pediatric Dermatology, 2013)
In infancy the skin problems resulting from self injuring behavior include highly variable clinical pictures, with various degree of severity. Some are very simple, like onychotillomania and onycophagia. The latter habits may be considered "normal", at least in some stages of development; others, such as trichotillomania, take on different meanings depending on the age at which they occur; moreover, others as dermatitis artefacta can cause permanent scars, and, however, represent a sign of significant psychosocial distress. Every pediatrician and dermatologist, finally, should know "Munchausen syndrome by proxy", a very rare psychopathological disorder, in which the young patient can present severe or even life-threatening damage.